2018
DOI: 10.3889/oamjms.2018.373
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for and Barriers to Attending Continuing Education Activities and Priorities for Different Dental Specialties

Abstract: BACKGROUND:Continuing education (CE) activities help dentists update their knowledge and skills to ensure high standards of patient care.AIM:This study aimed to evaluate the reasons for and barriers to attending CE activities including the priorities for different dental specialities.METHODS:The study involves a cross-sectional research design. After statistical consultation, a questionnaire was distributed among 323 dental practitioners in the Eastern province of Saudi Arabia. The questionnaire was checked fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…However, a survey of dental practitioners in Saudi Arabia indicated that lack of time, cost, and distance were the major barriers to attending continuing education activities. 31 Consistent with these findings, our study demonstrated that the most preferable method for Thai dentists to update their knowledge and promote rational drug use is through mobile applications. With the advances in technology, easily accessed pharmacological information is very important and requires little time and money.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, a survey of dental practitioners in Saudi Arabia indicated that lack of time, cost, and distance were the major barriers to attending continuing education activities. 31 Consistent with these findings, our study demonstrated that the most preferable method for Thai dentists to update their knowledge and promote rational drug use is through mobile applications. With the advances in technology, easily accessed pharmacological information is very important and requires little time and money.…”
Section: Discussionsupporting
confidence: 85%
“…The traditional way of continuing education conducted by educational institutions is through academic conferences and symposiums. However, a survey of dental practitioners in Saudi Arabia indicated that lack of time, cost, and distance were the major barriers to attending continuing education activities . Consistent with these findings, our study demonstrated that the most preferable method for Thai dentists to update their knowledge and promote rational drug use is through mobile applications.…”
Section: Discussionsupporting
confidence: 80%
“…15 However, lack of time was the most important barrier for dentists to attend continuing education activities. 9 The present study showed the dentists were more involved in continuing education during the COVID-19 epidemic, which may because they have more free time than previously. 7 The number of courses, duration and the number of participants increased significantly during the epidemic.…”
Section: Materials S and Me Thodsmentioning
confidence: 47%
“…Time is an important factor restricting dentist participation in continuing education. 23 During the pandemic, dental clinical work was greatly reduced, 3 providing dentists with more free time for continuing education. 5 In addition, synchronous courses are easily accessed, free from space constraints, and do not require face-to-face contact, helping to reduce the transmission risk of COVID-19.…”
Section: Discussionmentioning
confidence: 99%